Can a novel set of handgrips on a walking frame increase stability and support users when transferring to/from a chair? - Sibylle Brunhilde Thies; Susan Bevan; Matthew Wassall; Cynthia Poolay Mootien; Laurence Kenney; David Howard (BMC Geriatrics)
Abstract Introduction One important aspect of walking aid use is transferring safely to the aid from sitting and transferring back to the chair after walking, since these activities have been associated with falls in older adults. Standard frames require their user to push off the chair or ask for help from a carer, which may over time lead to back pain. This study’s aim was to assess whether novel handgrips located above the rear feet of a walking frame would facilitate safe transfer as compared to utilizing only the seat cushion or armrests of the chair. Methods In a gait lab-based trial 10 healthy older adults repeatedly transferred from sitting to standing, pushing off the chair’s seat cushion, armrests, or using the new lower handles on the frame (alone or in combination with the seat cushion or armrest). The stability margin ‘SM’, defined as the distance between the centre of pressure and the nearest edge of the base of support for the user-device-chair system, was calculated as a mechanical measure of stability. Specifically, SM provides a measure of how close the system is to the point of tipping over. Additionally, 13 older frame users tried to use the new handgrips to transfer to/from the new frame and gave interviews which were thematically analysed. Results Stability for the 10 healthy older adults was statistically either equivalent or better when using one or both handles on the novel frame as compared to pushing off the chair’s seat cushion or armrests. Amongst the 13 older frame users the frame’s new handgrips were useful to those living in the community and one person living in care, and they perceived them to facilitate independence and control. Discussion & conclusions The novel handgrips offer continuous support when getting up/sitting down and are well-received by those able to use them. The significance of the research lies in the reported number of falls during transfer from sitting to standing and vice versus, with underlying causes reported including loss of support. The proposed design is timely considering the documented increases in frailty and walking aid use in our ageing population.